PENGARUH LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN MELALUI ORGANIZATIOAN CITIZENSHIP BEHAVIOUR PADA PT TOBA PULP LESTARI SUMUT - Widjaja, Dennis; Tjendana, Martinus; Sunijati, Elisha; Anton, Anton (Jurnal Manajemen dan Bisnis, 2025)
This study aims to determine the Influence of Work Environment and Job Satisfaction on Employee Performance with Organizational Citizenship Behavior (OCB) as a Mediating Variable at PT Toba Pulp Lestari Sumut. This study uses a quantitative method with a population of 200 people and a sample of 133 people with Random Sampling Technique with the Slovin Formula. Data collection method through questionnaire distribution. Structural modeling using the Partial Least Squares (PLS) method is used for data analysis. Based on the results of the research that has been done, the work environment has a positive effect on employee performance and the influence of the work environment on employee performance with Organizational Citizenship Behavior (OCB) as a mediating variable is positive, thus the hypothesis can be accepted.